Toxicological evaluation of lactase derived from recombinant Pichia pastoris. - Shiying Zou; Xiaoyun He; Yifei Liu; Delong Chen; Yunbo Luo; Kunlun Huang; Wei Zhang; Wentao Xu (PLoS ONE, 2014)
A recombinant lactase was expressed in Pichia pastoris, resulting in enzymatic activity of 3600 U/mL in a 5 L fermenter. The lactase product was subjected to a series of toxicological tests to determine its safety for use as an enzyme preparation in the dairy industry. This recombinant lactase had the highest activity of all recombinant strains reported thus far. Acute oral toxicity, mutagenicity, genotoxic, and subchronic toxicity tests performed in rats and mice showed no death in any groups. The lethal dose 50% (LD50) based on the acute oral toxicity study is greater than 30 mL/kg body weight, which is in accordance with the 1500 L milk consumption of a 50 kg human daily. The lactase showed no mutagenic activity in the Ames test or a mouse sperm abnormality test at levels of up to 5 mg/plate and 1250 mg/kg body weight, respectively. It also showed no genetic toxicology in a bone marrow cell micronucleus test at levels of up to 1250 mg/kg body weight. A 90-day subchronic repeated toxicity study via the diet with lactase levels up to 1646 mg/kg (1000-fold greater than the mean human exposure) did not show any treatment-related significant toxicological effects on body weight, food consumption, organ weights, hematological and clinical chemistry, or histopathology compared to the control groups. This toxicological evaluation system is comprehensive and can be used in the safety evaluation of other enzyme preparations. The lactase showed no acute, mutagenic, genetic, or subchronic toxicity under our evaluation system.